Effects of Income and Fund Management of State Civil Apparatus on Bank Credit Granting (Case Study of the Academic Community of IAIN Manado) - Syarifuddin Mala (IAIN Manado, 2019)
AbstractThis study aims to examine and analyze the influence of income (x1), and the management of funds of the state civil apparatus (X2) on bank credit granting, a case study of the Academic Community of IAIN Manado. This research is a survey research conducted on the Academic Community of IAIN Manado. The population in this study is 111 respondents and the sample is 87 respondents. Sampling uses a random sampling technique with Solvin formula. The data analysis technique used in this study is the normality test, hypothesis testing, and T test using multiple regression analysis with SPSS V.16 application for Windows.The results of this study prove that income does not affect the granting of credit with a value of 0.857> 0.05, Fund management affects the granting of credit with a value of 0.003 <0.05 and Revenue (X1) and Fund Management (X2) simultaneously for Credit granting (Y ) with a value of 0.005 <0.05. Based on the results of the analysis it can be seen that the R square value is 0.119 or 11, 9% management of funds. This means that the influence of the fund management variable on the provision of bank credit has an influence of 11, 9%Keywords: Income, Fund Management, and Credit Granting